Dexamethasone Promotes a Stem-Like Phenotype in Human Melanoma Cells via Tryptophan 2,3 Dioxygenase - Cecchi, Marta; Mannini, Antonella; Lapucci, Andrea; Silvano, Angela; Lulli, Matteo; Luceri, Cristina; D’Ambrosio, Mario; Chiarugi, Alberto; Eid, Ali H.; Parenti, Astrid (Frontiers in Pharmacology, 2022)
In addition to its well-established immunosuppressive actions, tryptophan 2,3-dioxygenase (TDO) appears to elicit direct effects on tumor cell function. Although TDO has been associated with cancer stemness, its involvement in melanoma stem cell biology remains largely unknown. Since we showed that by upregulating TDO, dexamethasone (dex) promotes proliferation and migration of SK-Mel-28 human melanoma cells, we next sought to investigate dex effects on melanoma spherogenesis and stemness, and whether these events are mediated by TDO. We demonstrate here that dex significantly upregulates TDO in A375, a more aggressive melanoma cell line, confirming that dex effects are not limited to SK-Mel-28 cells. Moreover, dex stimulates spherogenesis of both cell lines, which is mediated by TDO, evident by its suppression with 680C91, a TDO inhibitor. The formed melanospheres appear to be enriched with embryonic stem cell marker mRNAs, the expression of which is potentiated by dex. Expression of cancer stem cell markers (CD133, CD44, GD2 ganglioside) was significantly increased in A375 spheres, as detected by flow cytometry. Taken together, our results suggest that TDO could represent a promising target in the management of melanoma and that dex, routinely used as a co-medication also in advanced melanoma, may stimulate melanoma cell function/tumor-supporting properties, a rather debilitating and undesired side effect.